2015
DOI: 10.1080/19420862.2015.1008351
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage efficient 2A peptides for high level monoclonal antibody expression in CHO cells

Abstract: (2015) Cleavage efficient 2A peptides for high level monoclonal antibody expression in CHO cells, mAbs, 7:2, 403-412, DOI: 10.1080/19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 Abbreviations: CHO, Chinese hamster ovary; HC, heavy chain; LC, light chain; mAb, monoclonal antibody; F2A, 2A peptide derived from the foot-and-mouth disease virus; E2A, 2A peptide derived from the equine rhinitis virus; P2A, 2A peptide derived from the porcine teschovirus-1; T2A, 2A peptide derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 44 publications
(95 reference statements)
4
140
0
Order By: Relevance
“…However, when we placed the LC gene upsreatm of the furin recognition site, we did not observe complete cleavage of furin. In agreement with our studies, several other investigations have also indicated that furin could not cleave efficiently when either LC or HC were arranged as a first cisteron [31, 44, 45]. Furthermore, different furin cleavage patterns were detected in the cell pools receiving either CHEF-F2A or CMV-F2A vectors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, when we placed the LC gene upsreatm of the furin recognition site, we did not observe complete cleavage of furin. In agreement with our studies, several other investigations have also indicated that furin could not cleave efficiently when either LC or HC were arranged as a first cisteron [31, 44, 45]. Furthermore, different furin cleavage patterns were detected in the cell pools receiving either CHEF-F2A or CMV-F2A vectors.…”
Section: Discussionsupporting
confidence: 92%
“…Considering these finding, it appears that factors other than the arrangement of the light and heavy chains affect the hydrolysis activity of furin. To give an illustration, Fang et al observed complete furin cleavage upon expression of mAb in vivo (Rat) [19] while furin could not cleave completely when mAbs were expressed in CHO and HEK 293T cells [31, 44, 45]. Also, some reports have demonstrated that secretory pathway of CHO cells is not able to provide sufficient amount of proteolytic enzymes to support the complete processing of the recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by mass spectromtery analysis, which detects 2A peptide at the 25‐kDa band and not the 50‐kDa band (data not shown). Partial cleavage of the FMDV 2A 24 amino acids residues by the furin protease following ribosome skipping was also reported by Chng et al By contrast, western blot analysis of serum derived from SCID mice that were implanted with the same TARGT‐adalimumab demonstrated two bands at 25 and 50 kDa, corresponding to the native antibody L and H chains at a size similar to adalimumab standard spiked into control SCID sera. This implies a serum derived furin enzyme cleavage, and confirms the correct processing of adalimumab in vivo .…”
Section: Discussionsupporting
confidence: 63%
“…One of approach is the introduction of the FMDV 2A ribosome skipping signal, between the light (L) and heavy (H) DNA coding sequences that enables equimolar expression of the two antibody separated chains. The addition of a furin cleavage site facilitated the separation of the two chains and the removal of the 2A–encoded additional amino acids …”
Section: Introductionmentioning
confidence: 99%
“…These plasmids encode multiple proteins in tandem, each separated by high efficiency cleavage sites of a 2A peptide derived from porcine teschovirus-1 ( Chng et al, 2015 ; Daniels et al, 2014 ; Kim et al, 2011 ). Studies using these engineered plasmids in human cell Lines, drosophila, zebrafish and mice have validated their use for the reliable co-expression of multiple constructs in diverse settings ( Chng et al, 2015 ; Daniels et al, 2014 ; Goedhart et al, 2011 ; Kim et al, 2011 ; Martin et al, 2006 ) . …”
Section: Introductionmentioning
confidence: 99%